2021
DOI: 10.1364/ol.418064
|View full text |Cite
|
Sign up to set email alerts
|

Efficient type II second harmonic generation in an indium gallium phosphide on insulator wire waveguide aligned with a crystallographic axis

Abstract: We theoretically and experimentally investigate type II second harmonic generation in III-V-on-insulator wire waveguides. We show that the propagation direction plays a crucial role and that longitudinal field components can be leveraged for robust and efficient conversion. We predict that the maximum theoretical conversion is larger than that of type I second harmonic generation for similar waveguide dimensions and reach an experimental conversion efficiency of 12%/W, limited by the propagation loss.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…2 for the pump (940 nm), idler (1550 nm), and signal (2389 nm). It is also observed that the longitudinal components are not negligible [47]. They are taken into account in the coupling coefficient given in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…2 for the pump (940 nm), idler (1550 nm), and signal (2389 nm). It is also observed that the longitudinal components are not negligible [47]. They are taken into account in the coupling coefficient given in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Three main integration routes, namely, bonding technology, heteroepitaxial growth, and flip-chip integration, are currently exploited. Wafer-bonding technologies require a root mean squared (RMS) roughness of 0.5 nm to achieve molecular adhesion or the use of adhesive layers, commonly BCB, which can induce stress and inhomogeneities . Similarly, the ≈8% lattice mismatch between III–V and Si leads to large defect densities in heteroepitaxial growth, partially overcome by the use of large buffer layers .…”
Section: Introductionmentioning
confidence: 99%
“…From an InGaP lattice-matched to GaAs nanolayer of 250 nm (1), InGaP WGs are patterned (2) for later AZ 4562 coating (3). A SiO 2 is coated with PMMA and AZ 4562 (4) for later pressing against the sample after adding diluted PR within the interface (5) to obtain a cross-linked interface (6). Finally, the GaAs substrate is back-etched (7), yielding suspended InGaP WGs (8).…”
Section: ■ Introductionmentioning
confidence: 99%